The Effectiveness of the Certificate of Inheritance Issued by the Sub-district in the Transfer of Land Rights Due to Inheritance in the Boyolali District Area - Hapsari, Anindya Ayu; Arifulloh, Achmad (TABELLIUS: Journal of Law, 2025)
Abstract. This study aims to analyze: 1) Procedures for the issuance of a Certificate of Inheritance issued by the sub-district in the transfer of land rights due to inheritance in the Boyolali District area. 2). Effectiveness of the Certificate of Inheritance issued by the sub-district in the transfer of land rights due to inheritance in the Boyolali District area.This type of research falls within the scope of empirical legal research. The approach used is a sociological-juridical approach. The data types and sources used are primary and secondary data, obtained from interviews and literature studies. The analysis is descriptive and analytical. The following conclusions are drawn from the research results: 1). Procedures for implementing the issuance of a Certificate of Inheritance issued by the sub-district in the transfer of land rights due to inheritance in the sub-district areaBoyolali includes applications, collecting administrative requirements, filling out forms or making a statement of heirs independently and ratification. 2) Problems occurred only once in Winong Village in 2019 where the applicant added data on heirs that were not real. This problem made the SKW declared invalid. Obstacles that often occur in Pulisen, Siswodipuran and Winong Villages are more related to internal problems of the applicant, such as the lengthy process of collecting the heirs' signatures. Effectiveness Analysis refers to the criteria for legal effectiveness according to Soerjono Soekanto which include legal factors, law enforcement, facilities, society, and culture. The Certificate of Inheritance in the transfer of inheritance rights issued by the village in Boyolali District shows significant effectiveness. Keywords: Certificate of Inheritance; Sub-district; Transfer of Rights.